Decision Modelling: An Objective Approach to Moral Reasoning - Cahn, Susanna (Teaching business ethics, 2003)
All agree that moral issues are difficult issues mired in philosophical, political, social, and spiritual values. It's no wonder that the process of calculating moral positions has been likened to ``eating broth with a fork.'' While insuring moral behavior is difficult, teaching moral reasoning, a noble act, is even more difficult – especially when confronted by students who, by nature or discipline, are essentially objectivists dependant upon a need to structure what most will agree defies structure. This paper suggests one way the use of decision modeling may reach to moral objectivists in a classroom setting.